Effects of an individualized mental-skills-training program on golf performance: A single-subject research design - Ashbrook, P. R.; Gillham, A.; Barba, D. (The Sport Psychologist, 2018)
Using a single-subject research design, a 1-to-1 tailored mental-skills-training (MST) program was created, implemented, and evaluated. During the 20-wk intervention phase, 6 National Collegiate Athletic Association Division I college golfers received a series of individually tailored MST sessions aimed at enhancing their mental skills and athletic performance. Each athlete`s golf performance, mental-skill frequency, and response to service were evaluated using visual inspection. Despite some limitations, results suggested that the 1-to-1 training program was effective, with nearly 50% of the performance and perception metrics improving from baseline and almost 80% of the mental skills improving. Follow-up analyses indicated that the program continued to positively affect performance into the next competitive season.